Soft composite hinge actuator and application to compliant robotic gripper. (1st August 2016) - Wang, Wei; Rodrigue, Hugo; Kim, Hyung-Il; Han, Min-Woo; Ahn, Sung-Hoon
Abstract: This work introduces the design of a smart soft composite (SSC) hinge actuator capable of a pure bending motion concentrated on specific sections of the actuator. This actuator makes use of a shape memory alloy (SMA) wire in a polydimethylsiloxane (PDMS) matrix embedded with segmented rigid components. The bending deformation was accomplished by actuating the SMA wire embedded along the length of the matrix eccentrically from neutral surface. This study introduces the design and manufacturing method of the actuator and experimental results for the maximum bending curvature for different configurations of the actuator. A model was presented to calculate the maximum bending curvature and validated against the experimental data. Results show that a smaller flexible length ratio is better for obtaining a larger maximum bending curvature, and that for an actuator containing multiple hinges, the total length of the hinges is more important than the number of hinges in the actuator. Finally, a gripper consisting of three fingers was developed where each finger consists of a hinge actuator with two hinges. The fingers of the gripper have a working length of 90 mm and the gripper was evaluated by grabbing cylindrical objects with diameters ranging between 1 mm and 80 mm. Results show that the gripper has a good passively adaptive capability for grasping a large range of objects with different sizes by virtue of the properties of the hinge actuator. Afterwards, the pulling force through different grasps was tested and it was shown that the gripper is capable from transitioning directly from a power grasping to a fingertip grasp and that power grasping is better than the fingertip grasp.